Mental Health and Well-being among Refugee-Aid Workers in Egypt - Khattab, Mahmoud (AUC Knowledge Fountain, 2023)
Refugee-aid workers are positioned in the middle between the realities and suffering of refugees and the detachment of the organizations and their donors. They carry the burden of accommodating both realities as the connecting link between both worlds. This study has found that the continuous exposure to the traumatic stories that refugees go through has negative implications on the mental health and well-being of the workers providing services to these refugees. Additionally, a lack of resources and negative management cultures impose stress on the refugee-aid worker. Negligence and failure by organizations to mitigate these stressors lead to a deterioration in the mental health state of the workers as well as the quality of services provided. Implications on mental health include symptoms of burnout, compassion fatigue and secondary traumatic stress, among other consequences. Consequentially, findings of the study have found that affected refugee-aid workers may refrain from providing the services to refugees and subject refugees to different forms of maltreatment and abuse. On the other hand, social and institutional support have been found to reduce the intensity of psychological distress and mediate the possible consequences on the quality of services provision.